Cutaneous lymphohistiocytic and multifocal lymphoma in an adult mare - SPANOUDES (Κ.Μ. ΣΠΑΝΟΥΔΗΣ) K. M.; McGOWAN, C. M.; DIAKAKIS (Ν.Ε. ΔΙΑΚΑΚΗΣ) N. E.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Cutaneous or subcutaneous lymphoma is one of the four different forms appearing in the horse. This type of equine lymphoma is usually lymphohistiocytic with a Τ, Β or mixed-cell immunophenotype and with a prevalence of less than 3% among skin neoplasms. This is all about a 9-year old Warmblood mare admitted with a 5-month history of multiple cutaneous masses spreading to many parts of the body. Apart from the multiple subcutaneous nodules and plaques, which did not provide discomfort to the horse, no other abnormalities were found either in clinical or laboratory examination. Lesionai histopathology and immunohistochemistry revealed a lymphohistiocytic T-cell lymphoma, which most likely was primary. The owner elected not to have her horse treated, but readmitted it for euthanasia 5 months later, because of the worsening of skin lymphoma and the appearance of general and systemic clinical signs. The ensuing postmortem was suggestive of distant metastatic disease (liver, mediastinal lymph nodes, pharyngeal wall) most likely originating from the skin.